2008
DOI: 10.1111/j.1399-5448.2008.00443.x
|View full text |Cite
|
Sign up to set email alerts
|

Insulin detemir is characterized by a more reproducible pharmacokinetic profile than insulin glargine in children and adolescents with type 1 diabetes: results from a randomized, double-blind, controlled trial*

Abstract: Original ArticleInsulin detemir is characterized by a more reproducible pharmacokinetic profile than insulin glargine in children and adolescents with type 1 diabetes: results from a randomized, double-blind, controlled trial* Danne T, Datz N, Endahl L, Haahr H, Nestoris C, Westergaard L, Fjording MS, Kordonouri O. Insulin detemir is characterized by a more reproducible pharmacokinetic profile than insulin glargine in children and adolescents with type 1 diabetes: results from a randomized, double-blind, contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 26 publications
(30 reference statements)
1
47
1
2
Order By: Relevance
“…Once daily insulin detemir has not been studied. Insulin detemir has a stable absorption profile, with day-to-day variability less than that of insulin glargine and markedly less than that of insulin NPH 5 6. When given once daily with breakfast, detemir has the potential to avoid hypoglycaemia (particularly nocturnal).…”
Section: Introductionmentioning
confidence: 99%
“…Once daily insulin detemir has not been studied. Insulin detemir has a stable absorption profile, with day-to-day variability less than that of insulin glargine and markedly less than that of insulin NPH 5 6. When given once daily with breakfast, detemir has the potential to avoid hypoglycaemia (particularly nocturnal).…”
Section: Introductionmentioning
confidence: 99%
“…Glargine has a duration of action independent of dose and should theoretically last longer for young patients taking small doses (<0.4 units/kg/day) than detemir, which has a dose-dependent duration of action [3]. However, two studies found lower within-subject variability with detemir, one of these studies being performed in children [5, 6]. Conflicting data exists as to the HbA1c lowering effect of detemir compared to glargine, with studies finding no difference, a decrease, and an increase [79].…”
Section: Discussionmentioning
confidence: 99%
“…Another study examined the AUC of insulin concentration in children and adolescents with type 1 diabetes. It found significantly less within-subject variability with detemir in comparison to glargine; however the measurements only continued for 16 hours after the dose and perhaps did not reflect the variable duration of detemir [6]. …”
Section: Introductionmentioning
confidence: 99%
“…for infants and toddlers who are reluctant to eat). Insulin detemir is approved for children above 2 years of age and has shown lowest within-subject variability,[30] reduced hypoglycemia rates, improved adherence, and greater treatment satisfaction. [2328]…”
Section: Treatment Approach For Management Of T1dmmentioning
confidence: 99%